Intensive insulin therapy combined with metformin is associated with reduction in both glucose variability and nocturnal hypoglycaemia in patients with type 2 diabetes. Issue 7 (13th July 2017) - Zhang, Yifei; Zhao, Zhiyun; Wang, Shujie; Zhu, Wei; Jiang, Yiran; Sun, Shouyue; Chen, Chen; Wang, Kai; Mu, Liangshan; Cao, Jinyi; Zhou, Yingxia; Gu, Weiqiong; et al.
Abstract: Background: The effect on glucose variability in patients with intensive insulin therapy has not been fully understood. This observational study investigated the different glucose variability and hypoglycaemia patterns in type 2 diabetes patients treated with continuous subcutaneous insulin infusion (CSII) or multiple daily injections (MDI) with or without metformin administration. Methods: During hospitalization, a total of 501 patients with poor glycaemic control and in initial treatment with either CSII alone ( n = 187), CSII + Metformin ( n = 81), MDI alone ( n = 146), or MDI + Metformin ( n = 87) were involved in the final analysis. Data obtained from continuous glucose monitoring were used to assess blood glucose fluctuation and nocturnal hypoglycaemia. Results: Among the 4 groups, no difference was found in mean blood glucose levels. Results in parameters reflecting glucose fluctuation: continuous overlapping net glycaemic action in CSII + Metformin and mean amplitude of glycaemic excursions in MDI + Metformin were significantly lower than those in either CSII alone or MDI alone, respectively, even after adjustment ( P = .031 and .006). Frequency of nocturnal hypoglycaemia was significantly decreased in CSII + Metformin as compared with CSII alone (0.6% vs 1.8%) and in MDI + Metformin as compared with MDI alone (1.6% vs 2.3%), with the highest frequency observed in MDI alone and the lowest in CSII + Metformin (all between group P < .001). Consistent results were obtained in between‐group comparisons for hypoglycaemia duration. Subgroup analysis matched with baseline body mass index, and glycated haemoglobin and fasting blood glucose further confirmed these findings. Conclusion: Metformin added to initial CSII or MDI therapy is associated with a reduction in both glucose fluctuation and nocturnal hypoglycaemic risk in patients with type 2 diabetes.